Transtibial Amputation with Removal of the Tibial Intramedullary Nail: Hardware Removal in a Retrograde Manner - Youn-Ho Choi; DoJoon Park (Case Reports in Orthopedics)
Transtibial amputation is the preferred strategy for treating a diabetic foot with an infection and necrosis. However, if a tibial intramedullary nail was previously inserted into the ipsilateral lower extremity, the nail must be removed to perform the transtibial amputation. In this special situation, the removal of the tibial intramedullary nail can cause various complications after transtibial amputation. We present a case and surgical technique report of a 46-year-old male with an uncontrolled diabetic foot with tibial intramedullary nail insertion. With the nail and ankle fixed by distal interlocking screws, a below-knee amputation was performed by removing the nail and the amputated limb together. This surgical method is expected to reduce postoperative complications such as infections and patella instability after the amputation of a diabetic foot.